UJI BEDA MANAJEMEN LABA SEBELUM DAN SELAMA KRISIS DI INDONESIA - Sanjaya, I Putu Sugiartha; Budi Raharjo, D. Agus (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2006)
Scott (2000) explained patterns of earnings management as taking a bath and income minimization. Taking a bath can be made during periods of organizational stress or reorganization, including the hiring of a new CEO. If a firm must report a loss, management may feel compelled to report a large one. Consequently, it will write off assets, provide for expected future costs, and generally clear of decks. This will enhance the probability of future reported profits. Income minimization is similar to taking a bath, but fewer extremes. A politically visible firm may choose patterns during periods of high profitability. Policies that suggest income minimization include rapid write-offs of capital assets and intangibles, expensing of advertising and R&D expenditures. The objective of this study is to investigate which pattern of earnings management chosen by management during economic crisis in Indonesia. Therefore, there are differences on earnings management between before the economic crisis and during the economic crisis in Indonesia. To test the hypothesis of this study, data are collected from Jakarta Stock Exchange for manufacturing companies. There are 27 companies. The result of this study suggests that management is most likely to make income decreasing to taking a bath.Keywords: earnings management, economic crisis, taking a bath, and income minimization.